RECEPCJA ESTETYCZNA POEZJI KONKRETNEJ NA LEKCJI JĘZYKA OBCEGO - Meinel, Katarzyna (Scripta Neophilologica Posnaniensia, 2019)
The subject of the article is the aesthetic reception of concrete poetry and the possibility of its use in foreign language classes. Reception aesthetics concentrates on the reception of the work and not its production. Concrete poetry works on sight and hearing, combines decoding of letters with visual perception and creates special opportunities for aesthetic reception in foreign language classes. The article draws attention to the phenomenon of text communication. The historical background and the first attempts to experiment with concrete poetry are discussed. Works of concrete poetry bring together aesthetics and didactics, which justifies their use in class. The functions and objectives of working with concrete poetry in the lesson are discussed and examples of works included in textbooks and examples of lesson scenarios are given.